Survei Manajemen Pengelolaan Stiper Edu Agro Tourism (SEAT) di Bawen Kabupaten Semarang (Universitas Negeri Semarang, 2021)
The presence of physical recreation facility in each area is designed modernly and uniquely adapted to the circumstances and natural surroundings, so as to provide a special message and impression to visitors. In addition to the facility that are designed modernly, you must also pay attention to the completeness, the quality, the safety and the comfort of the atmosphere within the facility. STIPER Edu Agro Tourism (SEAT) is a place that provides recreational services with various kinds of vehicle facilities. Recreational facilities require a management role to manage all existing resources. The purpose of this study is to determine the existing management role in STIPER Edu Agro Tourism Bawen, Semarang Regency. This study uses a qualitative descriptive approach. The subjects in this study were visitors who came to Stiper Edu Agro Tourism who had carried out outbound activities, data collection. Data collection thecniques were triangulation, data analysis was inductive/qualitative, and the results of qualitative research emphasized the meaning rather than generalization using the data collection method of observation, interviews, and documentation. Then the data analysis technique uses data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses triangulation of technical data by comparing the results of data collection. The results of this study showed that the existing management in STIPER Edu Agro Tourism has been organized both from its natural resources and human resources. The facilities in this place are also quite adequate, so that visitors who visit also feel comfortable doing recreational activities here. The conclusion of this study is that the management of Stiper Edu Agro Tourism is under the auspices of Instiper Yogyakarta. The management in that place uses four management processes, namely planning, organizing, actuating and controlling. Suggestions given by researchers are 1) For managers to fix and improve the existing sarpras facilities at Stiper Edu Agro Tourism 2) For employees who are assigned to STIPER Edu Agro Tourism to work responsibly and pay attention to every superior’s instructions to prevent miscommunication.